2014
DOI: 10.1111/bph.12784
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A activates hypoglossal motoneurons and enhances genioglossus muscle activity in rats

Abstract: Background and Purpose Orexins have been demonstrated to play important roles in many physiological processes. However, it is not known how orexin A affects the activity of the hypoglossal motoneuron (HMN) and genioglossus (GG) muscle. Experimental Approach GG muscle electromyograms (GG‐EMG) were recorded in anaesthetized adult rats after orexin A or orexin receptor antagonists were applied to the hypoglossal nucleus, and in adult rats in which orexin neurons were lesioned with the neurotoxin orexin‐saporin (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
2
10
0
1
Order By: Relevance
“…The fact that 1) orexin neurons are involved in sensing the body's external and internal environments (14-16) , 2) orexin neurons have a role in stimulating upper airway (17) and central respiratory neurons (12) , and 3) our findings showing increased orexin levels after bariatric surgery are all facts that support our speculation that neurophysiologic mechanisms may be responsible for the observed changes in OSA.…”
Section: Discussionsupporting
confidence: 80%
“…The fact that 1) orexin neurons are involved in sensing the body's external and internal environments (14-16) , 2) orexin neurons have a role in stimulating upper airway (17) and central respiratory neurons (12) , and 3) our findings showing increased orexin levels after bariatric surgery are all facts that support our speculation that neurophysiologic mechanisms may be responsible for the observed changes in OSA.…”
Section: Discussionsupporting
confidence: 80%
“…Microinjection of SB 334867 or TCS OX2 29 into the hypoglossal nucleus decreases the tonic genioglossus activity, which suggests the involvement of endogenous orexins in the regulation of genioglossus muscle activity in rats (Zhang et al . ). In addition, endogenous orexins also play important roles in food intake (Terrill et al .…”
Section: Discussionmentioning
confidence: 97%
“…Techniques used for medullary slice preparations were similar to those described previously for HMNs (Zhang et al . ). Briefly, the pups were anesthetized by chloral hydrate (5%), decapitated, and their brainstems were rapidly removed.…”
Section: Methodsmentioning
confidence: 97%
“…Our previous studies sustained the above hypothesis and revealed that, orexin A released from the hypothalamic orexinergic neurons increases GG activity via activation of orexin receptors in medullary HMNs (Zhang et al . ). Likewise, histaminergic drive, an important component of the arousal system (Huang et al .…”
mentioning
confidence: 97%